2014
DOI: 10.5897/ajb2013.12785
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mutagens on M1 population of black gram (Vigno mungo L. Hepper)

Abstract: This study was carried out with black gram (urdbean) variety TNAUCo(Bg)6 to determine the effects of gamma rays (150, 200, 250, 300 and 350 Gy) and ethyl methane sulphonate (10, 15, 20, 25, 30 mM). Data collected were on seed germination and survival, pollen and seed fertility, plant height, number of primary branches, number of clusters per plant, number of pods per plant, pod length, number of seeds per plant, hundred seed weight and yield per plant in M 1 generation. Thereafter, progressive reduction in ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…However, gamma radiation generally reduces the reproductive ability of the plant and increases the number of sterile pollen much more than the environmental effects. The results obtained were in accordance with the earlier reports of (Jain and Khandelwal, 2008) and (Ramya et al, 2014) in blackgram; (Khan et al, 2004) and (Singh and Singh, 2007) in greengram. The decrease in pollen fertility of rice after irradiation is considered to be due to chromosomal aberrations (Matsuo and Onozawa, 1961).…”
Section: Discussionsupporting
confidence: 92%
“…However, gamma radiation generally reduces the reproductive ability of the plant and increases the number of sterile pollen much more than the environmental effects. The results obtained were in accordance with the earlier reports of (Jain and Khandelwal, 2008) and (Ramya et al, 2014) in blackgram; (Khan et al, 2004) and (Singh and Singh, 2007) in greengram. The decrease in pollen fertility of rice after irradiation is considered to be due to chromosomal aberrations (Matsuo and Onozawa, 1961).…”
Section: Discussionsupporting
confidence: 92%
“…Similar effects on plant survival have been reported by Balai and Krishna (2009) in mungbean and Govardhan and Lal (2013) in field pea (Pisum sativum L.) and Rai et al (2013) in Linseed. Ramya et al (2014) carried out an experiment in black gram in M1 population and found the same results in pea. In the present study, the number of branches per plant of Sodium Azide administered M1 plants at maturity are presented in table 1.…”
Section: Resultsmentioning
confidence: 61%
“…In previous finding showed that LD50 value as 250 Gy of gamma rays in balck gram var. TNAUCo(Bg)6 (Ramya et al, 2014), 450 Gy in green gram var. CO 6 and CO 8 (Rukesh et al, 2017), 375.52 Gy in green gram var.…”
Section: Resultsmentioning
confidence: 99%